Systemic inflammatory responses following welding inhalation challenge test. (2015) - Kauppi, Paula; Järvelä, Merja; Tuomi, Timo; Luukkonen, Ritva; Lindholm, Tuula; Nieminen, Riina; Moilanen, Eeva; Hannu, Timo
Abstract: Aim: The aim of this study was to investigate inflammatory and respiratory responses to welding fume exposure in patients with suspected occupational asthma. Methods: Sixteen patients referred to the Finnish Institute of Occupational Health underwent mild steel (MS) and stainless steel (SS) welding challenge tests, due to suspicion of OA. Platelet count, leucocytes and their differential count, hemoglobin, sensitive CRP, lipids, glucose and fibrinogen were analyzed in addition to interleukin (IL)-1β, IL-6, IL-8, TNF-α, endothelin-1, and E-selectin in plasma samples. Peak expiratory flow (PEF), forced expiratory volume in 1 min (FEV1 ) and exhaled nitric oxide (NO) measurements were performed before and after the challenge test. Personal particle exposure was assessed using IOM and a mini sampler. Particle size distribution was measured by an Electric Low Pressure Impactor (ELPI). Results: The number of leukocytes, neutrophils, and platelets increased significantly, and the hemoglobin level and number of erythrocytes decreased significantly after both the MS and SS exposure tests. Five of the patients were diagnosed with OA, and their maximum fall in FEV1 values was 0.70 l (±0.32) 4 h after SS exposure. MS welding generated an average inhalable particle mass concentration of 31.6, and SS welding of 40.2 mg/m 3 . The mean particle concentration measured inside the welding face shields by the mini sampler was 30.2 mg/m 3 and 41.7 mg/m 3, respectively. Conclusions: Exposure to MS and SS welding fume resulted in a mild systemic inflammatory response. The particle concentration from the breathing zones correlated with the measurements inside the welding face shields.